The Effect of Iodine Status on the Risk of Thyroid Nodules: A Cross-Sectional Study in Zhejiang, China - Xiaoming Lou; Xiaofeng Wang; Zhifang Wang; Guangming Mao; Wenming Zhu; Yuanyang Wang; Xuejiao Pan; Zhijian Chen; Zhe Mo (International Journal of Endocrinology)
Objective. The aim of this study was to explore whether iodine nutrition is associated with the risk of thyroid nodules among adult population in Zhejiang Province, China. Methods. A cross-sectional study was conducted in the general population aged 18 years or older. A total of 2,710 subjects received physical examination, questionnaires, and thyroid ultrasonography. Urinary iodine concentration (UIC) and thyroid hormone levels were measured and documented for each subject. 4 multiple logistic regression models adjusted for other risk factors were applied to analyze the association between iodine nutrition and thyroid nodules. Results. The prevalence of thyroid nodules was 15.5% among all adults. As indicated by all 4 models, subjects with UIC varying from 200 μg l−1 to 399 μg l−1 had lower risk of thyroid nodules compared with those with relatively low UIC (<100 μg l−1), with approximately 37–57 percent reduction in risk. Moreover, subjects with UIC between 100 and 199 μg l−1 had a decreased risk of thyroid nodules in model 1 and 2 (OR = 0.75, 95% CI, 0.58–0.97; OR = 0.75, 95% CI, 0.58–0.97, respectively). However, there was no significant difference of risk in thyroid nodules between subjects with high UIC (≥400 μg l−1) and low UIC (<100 μg l−1). Furthermore, intake of iodized salt was inversely associated with risk of thyroid nodules, with approximately 69–77 percent reduction in risk. Conclusion. The relationship between UIC and the risk of thyroid nodules is U-shaped. Consumption of noniodized salt is an independent risk factor of thyroid nodules.